2021
DOI: 10.21037/apm-21-329
|View full text |Cite
|
Sign up to set email alerts
|

Effect analysis of embracing breast milk sucking to relieve pain of neonatal heel blood sampling: a randomized controlled trial

Abstract: Background: Heel blood sampling of newborns plays an important role in the diagnosis of neonatal hypothyroidism, phenylketonuria, and other inherited metabolic diseases. Embracing breast milk sucking (EBMS) can increase the newborn's sense of security and can relieve pain. The purpose of the present study was to explore the effect of EBMS on alleviating the pain of neonatal heel blood sampling.Methods: A total of 96 neonates undergoing heel blood screening were selected from June 2019 to June 2020, and were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…During the procedure, a high level of pain was found for newborns in the breast milk odour group, a mild pain for those in the mother's heartbeat sounds group, and a very low pain for those in the breastfeeding group. These results are similar to those in the literature, where studies have reported lower pain scores for breastfeeding and breast milk odour compared to other methods (Nurbayanti, 2021;Peng et al, 2018;Wu et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…During the procedure, a high level of pain was found for newborns in the breast milk odour group, a mild pain for those in the mother's heartbeat sounds group, and a very low pain for those in the breastfeeding group. These results are similar to those in the literature, where studies have reported lower pain scores for breastfeeding and breast milk odour compared to other methods (Nurbayanti, 2021;Peng et al, 2018;Wu et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In one study, higher first attempt blood sampling success and higher SPO2, shorter blood draw and bleeding times and lower pain scores were reported for term infants who were breastfed in the mother's lap during heel lance procedures (Wu et al, 2021). Cirik and Efe (2020) compared six groups in different combinations of non‐pharmacological methods during orogastric (OG) tube insertion, and reported ‘breast milk + swaddling’ as the most effective method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al [ 30 ] described the development and validation of a multiplex SNaPshot minisequencing method to detect common mutations in the PAH gene in Iranian patients with PKU. The multiplex SNaPshot assay allows for the simultaneous analysis of multiple single nucleotide polymorphisms (SNPs) in a single reaction.…”
Section: Reviewmentioning
confidence: 99%